2022
DOI: 10.1038/s41467-022-32670-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-omics reveals cellular and molecular interactions governing the invasive niche of basal cell carcinoma

Abstract: Tumors invade the surrounding tissues to progress, but the heterogeneity of cell types at the tumor-stroma interface and the complexity of their potential interactions hampered mechanistic insight required for efficient therapeutic targeting. Here, combining single-cell and spatial transcriptomics on human basal cell carcinomas, we define the cellular contributors of tumor progression. In the invasive niche, tumor cells exhibit a collective migration phenotype, characterized by the expression of cell-cell junc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…The mechanisms by which aggressive BCCs develop are beginning to be fully elucidated. It was recently reported that transcriptional reprogramming occurs at the leading edge of the tumor–stroma interface in infiltrative BCC cases, thereby giving rise to tumor cells with a collective migratory phenotype and cancer-associated fibroblasts with extracellular matrix remodeling properties [ 25 ]. Moreover, the activin A signaling pathway regulates transcriptional tumor–stroma interactions and spatial organization.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which aggressive BCCs develop are beginning to be fully elucidated. It was recently reported that transcriptional reprogramming occurs at the leading edge of the tumor–stroma interface in infiltrative BCC cases, thereby giving rise to tumor cells with a collective migratory phenotype and cancer-associated fibroblasts with extracellular matrix remodeling properties [ 25 ]. Moreover, the activin A signaling pathway regulates transcriptional tumor–stroma interactions and spatial organization.…”
Section: Discussionmentioning
confidence: 99%
“…35 In basal cell carcinoma (BCC), the tumour-stroma interface was genetically separated, with a total of 86 genes found to be differentially expressed between the infiltrative and nodular tumour regions. 34 A high percentage of the genes was observed in a fibroblast cluster which was reported to drive BCC infiltration. 34 The spatial genomic landscape of tissues in clinical trials and drug development and testing can be particularly useful in identifying specific areas responsive to the drug and deciphering pathways that are associated with each response.…”
Section: Skin Cancermentioning
confidence: 99%
“…34 A high percentage of the genes was observed in a fibroblast cluster which was reported to drive BCC infiltration. 34 The spatial genomic landscape of tissues in clinical trials and drug development and testing can be particularly useful in identifying specific areas responsive to the drug and deciphering pathways that are associated with each response. Head and neck squamous cell carcinomas (HNSCC) are classified as the most common malignancies in the pharynx, larynx and oral cavity.…”
Section: Skin Cancermentioning
confidence: 99%
See 2 more Smart Citations